Kajian Kuat Tekan dan Modulus Elastisitas Pada Beton Variasi Limbah Granit Sebagai Substitusi Parsial Agregat Kasar - Najwa; Wibowo; Endah Safitri (Sustainable Civil Building Management and Engineering Journal, 2026)
One of the key aspects of construction is the use of concrete, making research to improve its quality highly necessary. This study uses recycled aggregate in the form of granite waste as a partial substitute for coarse aggregate to produce environmentally friendly concrete while maintaining its quality. The aim of this research is to determine the effect of varying granite waste content on the compressive strength and modulus of elasticity of concrete. The experimental method is used in this research, which focuses on concrete with granite waste variations of 0%, 15%, 30%, and 45%. Testing the compressive strength and modulus of elasticity of concrete using cylindrical specimens with a diameter of 15 cm and a height of 30 cm with a Compression Testing Machine and an additional dial gauge to measure specimen deformation. The compressive strength tests for concrete with granite waste variations of 0%; 15%; 30%; and 45% result in values of 22,27 MPa; 23,26 MPa; 29,27 MPa; and 25,28 MPa, respectively. Meanwhile, the modulus of elasticity tests yield values of 21727,29 MPa; 21882,92 MPa; 25920,23 MPa; 22585,91 MPa, respectively.